Comparison of microbial and chemical changes in common carp (Cyprinus carpio) fillets reared in earthen basins, river cages and river fish during storage in refrigerator - Ahmed A. Hussein; Itlal Hakim Almasoodi; Aqeel H. Atallah (Journal of Kerbala for Agricultural Sciences, 2024)
The factors that greatly affect the quality of fish meat are type of nutrition and nutritional conditions, their effects are found in the muscle structure and stability of fish meat during the storage period. To conduct this study, fish were stored for 14 days at a temperature of 4 °C. During the refrigerated storage period of fish fillets, the approximate composition of fish fillets (moisture, protein, fat and ash) was measured, and the quality factors of fish were recorded. The results also showed that the highest amount of moisture and the lowest amount of fat were in fish cultured in earthen ponds, and the amount of protein did not change significantly between the different treatments, the amounts of TBA, FFA and TVN increased during the refrigerated storage period, and the pH changes were not regular between the different treatments. The highest amount of TBA and FFA was between the different treatments. It was also noted that the highest amount of moisture was in river fish. Comparison of the results of the different qualitative factors between the three treatments showed that treating fish in an earthen pond environment compared to the two treatments is more susceptible to spoilage during the refrigerated storage period. While the microbiological studies were conducted.